Efficacy of Different Botanicals and Carbendazim in Managing Anthracnose (Colletotrichum lindemuthianum) in Green Gram (Vigna radiata L.) - Yashika Srivastava; Sujeet Pandey; Abhilasha. A. Lal; Shubham Singh; Atul Suresh Bawane (Archives of Current Research International, 2025)
A field trial was conducted during the Kharif season of 2023 at the Central Research Field, Department of Plant Pathology, Naini Agricultural Institute, Sam Higginbottom University of Agriculture, Technology and Sciences, Prayagraj, Uttar Pradesh. The objective was to evaluate the effectiveness of different botanicals in combination with 50 WP carbendazim against anthracnose disease caused by Colletotrichum lindemuthianum in green gram (Vigna radiata L.). Experimental results showed that all treatments significantly improved yield compared to the untreated control. The highest yield was recorded in T6 comprising (Carbendazim alone as seed and foliar treatment) recorded 11.23 q/ha which was followed by T1 (Carbendazim + Neem oil) to the tune of 9.23 q/ha and 8.73 q/ha. In control plot i.e (T0) yielded the lowest at 6.03 q/ha. In terms of cost-benefit ratio (CBR), T6 again showed the highest economic return (1:3.54), followed by T1 (1:2.90), and T2 (1:2.52). The control recorded a lower CBR of 1:2.02. The study highlights the potential of integrating botanicals like neem and eucalyptus oil with carbendazim for effective and economical management of anthracnose in green gram.